Temperature Cross in Three-Fluid Cryogenic Heat Exchangers. (February 2020) - Krishna, V; Seetharamu, K N; Spoorthi, S; Akshobhya,; Sukruth, R; Manoj, M; Murali, Prashanth; Bharadwaj, Prerak; Nayak, Subhash
Abstract: In multi-fluid heat exchangers, local equalization of fluid temperatures occur(s) at certain location(s) within the heat exchanger, depending on the chosen values of the operating condition parameters and design parameters. This is referred to as a 'temperature cross' between the concerned fluids. The formation of the temperature cross leads to a situation wherein there is reversal of heat transfer in the heat exchanger section on one side of the cross. A three-fluid cryogenic heat exchanger, involving thermal interaction between all the three-fluids - hot, cold and intermediate - is investigated for the effect of the temperature cross, for the different flow arrangements. Non-dimensional governing equations are formulated to account for ambient heat-in-leak and longitudinal wall conduction and solved using finite element method. An algorithm, using MATLAB, has been used to determine the position of the temperature cross. The variation of the temperature cross is investigated for varying values of the Thermal Resistance Ratio between intermediate-cold fluids and hot-cold fluids (H1).